1988
DOI: 10.1172/jci113666
|View full text |Cite
|
Sign up to set email alerts
|

Importance of adenosine triphosphate in phospholipase A2-induced rabbit renal proximal tubule cell injury.

Abstract: The pathogenesis of ischemic renal tubular cell injury involves a complex interaction of different processes, including membrane phospholipid alterations and depletion of high-energy phosphate stores. To assess the role of membrane phospholipid changes due to activation of phospholipases in renal tubule cell injury, suspensions enriched in rabbit renal proximal tubule segments were incubated with exogenous phospholipase A2 (PLA2). Exogenous PLA2 did not produce any significant change in various metabolic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…It has been widely suggested that phospholipase A2-generated phospholipid by-products, most notably fatty acids and lysophospholipids, participate in the evolution of acute renal tubular cell injury (12)(13)(14)(15)(16)(17). However, that sphingolipid metabolites/breakdown products have potent signaling effects raises the possibility that they, too, could be involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been widely suggested that phospholipase A2-generated phospholipid by-products, most notably fatty acids and lysophospholipids, participate in the evolution of acute renal tubular cell injury (12)(13)(14)(15)(16)(17). However, that sphingolipid metabolites/breakdown products have potent signaling effects raises the possibility that they, too, could be involved.…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic feature of acute toxic and ischemic renal tubular cell injury is partial degradation of membrane lipid constituents, leading to the accumulation of lipid by-products (12)(13)(14)(15)(16)(17). This suggests that the sphingomyelinase/ceramide/ sphingosine pathway could be involved in acute cell injury and repair.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of intracellular phospholipase A2 (PLA2)' has been implicated as an important biochemical mechanism responsible for accelerated phospholipid hydrolysis during renal ischemia (1)(2)(3)(4)(5). The vast majority of previous studies of the PLA2 1. Abbreviations used in this paper: AA, arachidonic acid; Compound 1, 1-3-(E)-6-(bromomethylene)-(tetrahydro-3-( 1-naphthalenyl)-2H-pyran-2-one; LDH, lactate dehydrogenase; PLA2, phospholipase A2.…”
Section: Introductionmentioning
confidence: 99%
“…Our previously reported data led us to conclude that PLA2 activation, consequent to calcium and reactive oxygen species exposure during reoxygenation, played an important role in electron transport chain damage localized to NADH coenzyme Q reductase, decreased F,-ATPase activity, decreased ADP-ATP translocase activity, and increased mitochondrial membrane permeability to H+ ions (3,6). Exogenous PLA2 treatment of hypoxic proximal tubules results in severe cellular injury and significant decreases in uncoupled respiratory rates of the tubules, reflective of electron transport chain damage (9).…”
Section: Introductionmentioning
confidence: 99%